2016
DOI: 10.1016/j.chc.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences, Resilience and Mindfulness-Based Approaches

Abstract: Synopsis US children with emotional, mental, or behavioral conditions (EMB) have disproportionate exposure to potentially traumatizing adverse childhood experiences (ACEs) (70.7% EMB vs. 46.9% non-EMB). Neuroscience, epigenetic, developmental, social, epidemiologic, and other sciences provide theoretical and empirical explanations for observed early and lifelong physical, mental, emotional, educational, and social impacts of the trauma and chronic stress that can result from ACEs. Together, these sciences poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(71 citation statements)
references
References 20 publications
6
65
0
Order By: Relevance
“…This lower rate is similarly predictive of whether a child has an EMB problem, defined using similar methods as reported in recent studies. 28 We found that among children with 4 or more ACEs, 37% are identified as having EMB for the reduced NSCH-ACEs compared with 39% with EMB for the full NSCH-ACEs (adjusted odds ratios are 4.65 and 5.02 respectively). As shown in Figure 2, multivariate regression analyses reveal that although the 3 topics in question are less predictive, individual NSCH-ACEs items do not vary dramatically in their power to predict whether a child has an EMB problem and that cumulative NSCH-ACEs scores are more powerful predictors compared with any single item.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…This lower rate is similarly predictive of whether a child has an EMB problem, defined using similar methods as reported in recent studies. 28 We found that among children with 4 or more ACEs, 37% are identified as having EMB for the reduced NSCH-ACEs compared with 39% with EMB for the full NSCH-ACEs (adjusted odds ratios are 4.65 and 5.02 respectively). As shown in Figure 2, multivariate regression analyses reveal that although the 3 topics in question are less predictive, individual NSCH-ACEs items do not vary dramatically in their power to predict whether a child has an EMB problem and that cumulative NSCH-ACEs scores are more powerful predictors compared with any single item.…”
Section: Resultsmentioning
confidence: 75%
“…28 Findings from this earlier study were replicated for each of the outcomes of focus in this analysis (CSHCN-More Complex, EMB, School Engagement, Resilience). Figure 3 shows findings for the “More complex CSHCN” outcome variable.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Less parenting stress, increased parental warmth, and increased parental attention to their children may also contribute to buffering against the poor health outcomes associated with ACEs [10,91]. Given the number of studies that suggest mindfulness may reduce parental dismissal of their children, mindful parenting may also contribute to resilience against trauma [92].…”
Section: Mindfulnessmentioning
confidence: 99%
“…It may be beneficial to consider methodology of mindfulness implementation that addresses their caretakers. Given that mindful parenting yields reduced parental stress, with increased parental warmth toward their children [10,91], suggests that mindful parenting training should also be included in interventions for youth. However, many caretakers are involved in influencing children.…”
Section: Mindfulness Program Considerationsmentioning
confidence: 99%